We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
206
2
avatar

(Part 1) Find polynomial f(n) such that for all integers n>=1, we have 3(1*2+2*3+...+n(n+1))=f(n). Write f(n) as a polynomial with terms in descending order or n.

 

(Part 2) The closed form sum of 12[1^2*2+2^2*3+...+n^2(n+1)] for n>=1 is n(n+1)(n+2)(an+b). Find an+b.

 May 23, 2018
 #1
avatar+22572 
0

(Part 1)

Find polynomial f(n) such that for all integers n>=1, we have 3(1*2+2*3+...+n(n+1))=f(n).

Write f(n) as a polynomial with terms in descending order of n.

 

\(\begin{array}{|rcll|} \hline f(n) &=& 3\cdot[~ 1\cdot 2 + 2\cdot 3 + 3\cdot 4 + 4\cdot 5 + \dots +n(n+1)~] \\ f(n) &=& 3\cdot[~ 1\cdot (1+1) + 2\cdot (2+1) + 3\cdot (3+1) + 4\cdot (4+1) + \dots +n(n+1)~] \\ f(n) &=& 3\cdot[~ (1^2+1) + (2^2+2) + (3^3+3) + (4^2+4) + \dots +(n^2+n)~] \\ f(n) &=& 3\cdot[~ (1+2+3+4+ \dots +n) + (1^2+2^2+3^3+4^2 + \dots +n^2)~] \\\\ && (1+2+3+4+ \dots +n) = \frac{(1+n)\cdot n}{2}\\ && (1^2+2^2+3^3+4^2 + \dots +n^2)= \frac{n\cdot(n+1)\cdot(2n+1)}{6} \\\\ f(n) &=& 3\cdot[~ \frac{(1+n)\cdot n}{2} + \frac{n\cdot(n+1)\cdot(2n+1)}{6}~] \\ f(n) &=& 3\cdot n \cdot(n+1)\cdot[~ \frac{1}{2} + \frac{(2n+1)}{6}~] \\ f(n) &=& 3\cdot n \cdot(n+1)\cdot[~ \frac{3}{6} + \frac{(2n+1)}{6}~] \\ f(n) &=& 3\cdot n \cdot(n+1)\cdot( \frac{3+2n+1}{6} ) \\ f(n) &=& 3\cdot n \cdot(n+1)\cdot( \frac{2n+4}{6} ) \\ f(n) &=& 3\cdot n \cdot(n+1)\cdot 2\cdot( \frac{n+2}{6} ) \\ \mathbf{f(n) }&\mathbf{=} &\mathbf{ n \cdot (n+1)\cdot (n+2)} \\ \hline \end{array}\)

 

Terms in descending order of n

\(\boxed{f(n) = n^3+3n^2+2n}\)

 

laugh

 May 24, 2018
edited by heureka  May 24, 2018
 #2
avatar+22572 
0

(Part 2)

The closed form sum of 12[1^2*2+2^2*3+...+n^2(n+1)] for n>=1 is n(n+1)(n+2)(an+b).
Find an+b.

 

\(\begin{array}{|rcll|} \hline && \mathbf{12 \left[1^2\cdot 2 + 2^2\cdot 3 + 3^2\cdot 4 +\ldots +n^2 \cdot (n+1)\right] } \\ &=& 12\sum \limits_{k=1}^{n} k^2 \cdot (k+1) \\ &=& 12\sum \limits_{k=1}^{n} (k^3 + k^2) \\ &=& 12\left[\sum \limits_{k=1}^{n} (k^3) + \sum \limits_{k=1}^{n} (k^2) \right] \\ && \begin{array}{|rcll|} \hline \sum \limits_{k=1}^{n} (k^3) &=& 1^3+2^3+3^3+ \ldots + n^3 = \left(\frac{n(n+1)}{2}\right)^2 \\ \sum \limits_{k=1}^{n} (k^2) &=& 1^2+2^2+3^2+ \ldots + n^2 = \frac{n(n+1)(2n+1)}{6} \\ \hline \end{array} \\ &=& 12\left[ \left(\frac{n(n+1)}{2}\right)^2 + \frac{n(n+1)(2n+1)}{6} \right] \\ &=& 12n(n+1)\left[ \frac{n(n+1)}{4} + \frac{2n+1}{6} \right] \\ &=& 12n(n+1)\left[ \frac{n(n+1)}{4} + \frac{2n+1}{2\cdot 3} \right] \\ &=& 12n(n+1)\left[ \frac{n(n+1)}{4} + \frac{n+\frac12}{3} \right] \\ &=& 12n(n+1)\left[ \frac{3n(n+1)+4n+2}{12} \right] \\ &=& n(n+1)[3n(n+1)+4n+2] \\ &=& n(n+1)[3n(n+2)-3n+4n+2] \\ &=& n(n+1)[3n(n+2) + n+2] \\ &\mathbf{=}& \mathbf{ n(n+1)(n+2)(3n+1) } \\ \hline \end{array} \)

 

\(\mathbf{\large{an+b = 3n+1}}\)

 

laugh

 May 24, 2018

7 Online Users